International lending, risk, and the Euromarkets - Angelini, Anthony; Eng, Maximo; Lees, Francis A. (New York : Wiley, 1979)
The book reviews the trends in international lending in the past years. It also analyses the growth and impact of US international lending after the Second World War, and discusses the new challenges facing international lenders at present.
"A Halsted Press book."
Includes bibliographical references and index.
usc 21/9/17
Loans
Keywords: Loans, Foreign; Loans, Foreign; Euro-dollar market; Euro-bond market